Analisis Cargo Loss pada Saat Bongkar Muatan Fame di PT. Sinarmas LDA Maritime - Indah Berliana Br. Sinaga; Frisca Mareyta Pongoh; Kriswanto Kriswanto; Iksan Saifudin; Yeddy Teddy Ombuh (Politeknik Pelayaran Sulawesi Utara, 2025)
To support the smooth operation of maritime transportation, particularly in the transportation of liquids such as FAME oil, factors that can influence cargo loss must be properly managed. Deterioration in quality or loss of cargo volume can occur for several technical and non-technical reasons. One of the main factors causing FAME cargo loss is a leak in the ship's hull or poorly maintained tank structures, resulting in partial cargo loss during the voyage. Furthermore, inappropriate vessel characteristics, such as suboptimal carrying capacity, are also a major cause of cargo loss. Inaccurate unloading and unloading procedures, such as careless handling, also contribute to this problem. The impact of FAME cargo loss is significant, both financially and on the company's reputation. Claims received from charterers regarding losses can be detrimental to the company, and decreased customer confidence can impact shipping volumes and revenue. To minimize the risk of cargo loss, companies need to implement effective strategies, such as routinely inspecting vessels and storage tanks to ensure there are no leaks. Training crews in proper loading and unloading procedures is also crucial to avoid human error that can lead to losses. Implementing a regular visual and technical inspection system will improve operational quality and minimize cargo loss during FAME transportation. Furthermore, the use of more advanced monitoring technology, such as sensors to detect leaks or changes in tank pressure, can help detect problems early. Data-driven maintenance management systems can also be used to monitor vessel condition and optimize maintenance schedules, thereby reducing the risk of damage that could lead to cargo loss.